1990
DOI: 10.3928/0098-9134-19901101-07
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Management Training for Nurse Aides: Is it Effective?

Abstract: Nursing assistants are responsible for 80% to 90% of all direct resident care in nursing homes, but are the least well trained personnel. Even with currently mandated training, specific skills to meet mental health needs are not taught. Training in behavior management skills prepares aides to observe and respond to problem behaviors more effectively. Aides view their own use of skills as increased by this training. To be practically useful, mental health training programs for nurse aides should be provided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…This is not surprising and a common finding in the literature (Cohn, Horgas, & Marsiske, 1990;McCallion, Toseland, Lacey et al, 1999). In most studies, including follow-ups, no long-term effects could be confirmed (Campbell, Knight, Benson et al, 1991;Maxfield, Lewis, & Cannon, 1996).…”
Section: Discussionmentioning
confidence: 54%
“…This is not surprising and a common finding in the literature (Cohn, Horgas, & Marsiske, 1990;McCallion, Toseland, Lacey et al, 1999). In most studies, including follow-ups, no long-term effects could be confirmed (Campbell, Knight, Benson et al, 1991;Maxfield, Lewis, & Cannon, 1996).…”
Section: Discussionmentioning
confidence: 54%
“…Canada is not alone in regard to deficiencies in dementia care (Hallberg et al 1995; Ford & McCormack 2000; Bostrom et al 2006). Across the globe, many strategies have been evaluated for their effect on improving care, including staff training, in Canada (Hagen & Sayers 1995) and the United States (Cohn et al 1990; Cohen‐Mansfield et al 1997), systematic clinical supervision in Sweden (Olsson et al 1998; Berg & Hansson 2000), formal staff motivational systems in the United States (Burgio et al 2002), and practice development in the United Kingdom (Wright & McCormack 2001). These different strategies have produced variable results and have led, at best, to short‐lived improvements in dementia care practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many of the studies we reviewed used external experts to reinforce good practice. Their independence of the day-to-day staff and management structure was found to be more effective in reinforcing good practice (Marsiske 1989;Cohn 1990;Depla 2003). Visiting psychiatrists are in a good position to act as such 'external experts'.…”
Section: The Psychiatrist's Role In Effective Trainingmentioning
confidence: 99%
“…In the scenario of Mr P, the psychiatrist and CPN had an opportunity to suggest to the managers that all the carers, not just the senior ones, and any staff members who had regular direct contact with people with dementia, should have access to basic training. The public display of certificates of attendance at training courses is not sufficient evidence that all current members of staff have received training and that the skills learnt are reinforced day-to-day throughout the care home (Cohn 1990;Stevens 1998;Banazak 2000;Burgio 2001.…”
Section: Accessible Trainingmentioning
confidence: 99%